Extração de metais em rejeitos de mineração de carvão fóssil através de lixiviação ácida assistida por ultrassom - Baum, Caroline Isabel (2018)
The beneficiation of fossil coal is a process that generates a large volume of tailings with about 50% of the crude coal extracted in Brazil, discarded. Therefore, it is important to develop techniques to reuse these wastes, adding value and reducing the final volume and environmental impact in the disposal. This work aims the study of a method of extracting metals in tailings from fossil fuel processing using acid leaching and ultrasound. The rejects were analyzed by ICP-OES (Optical Emission Spectrometry with Inductively Coupled Plasma) for the determination of Al, Fe, Zn, Cr and Ni. Subsequently, the effects of the use of H2O2, H2SO4 and HCl with HNO3 as the extraction solution were evaluated, in addition to the experimental variables, pH, ultrasound power, temperature and contact time, in order to achieve the best process leaching efficiency. The highest efficiencies obtained for the majority of the metals were with contact time of 60 minutes, average temperature of 80°C, amplitude of 20% and using extractive solution formed of 3% HNO3 and 2% of HCl, reaching values of approximately 15%, 4%, 7% and 1% leaching to Al, Fe, Cr and Ni. Zn presented efficiencies of up to 100%, however it was the metal that less suffered influence with respect to the parameters analyzed.